Comparison of ground reaction forces and joint kinematics between three different tempos during push-up exercise - Degirmen Yahya Berk; Erman Berkant; Ozkol Mehmet Zeki; Vural Faik; Aksit Tolga (Sciendo, 2022)
This study was aimed to analysis in detail how different tempos [2:0:2 (30 bpm), 1:0:1 (60 bpm), Explosive (EXP)] effect to ground reaction forces (vGRF) and joint kinematics of push-up exercise (PUP).